Il cammino della Chiesa per una rinnovata dottrina sociale: dal diritto di proprietà ai diritti sacri alla terra, alla casa, al lavoro (Stato, Chiese e pluralismo confessionale, 2018)
SOMMARIO: 1. La storia della dottrina sociale nella storia della Chiesa – 2. Dal diritto (esclusivo) di proprietà al riconoscimento dei diritti del lavoratore – 3. La questione sociale diventa questione universale – 4. Contatti tra la dottrina sociale e le teorie politiche del lavoro – 5. I tre diritti “sacri” per (re)inventare una nuova dottrina sociale.The Church’s path for an updated social doctrine: from the right to property to the sacred rights to land, housing and workABSTRACT: The essay analyzes the historical and juridical development of the Catholic Church’s social doctrine, from the teaching of Pope Leo XIII to the teaching of Pope Francis. Paying attention to the fundamental issues of the social justice is at the core of the existence and the mission of the Church. Nowdays, Pope Francis changed the emphasis of the official social doctrine, calling for a poor Church at the service of the poor and the Earth. This updated social doctrine is founded on the joyful announcement of the Gospel.
Keywords: Diritto canonico